Antibody targets in autoimmune encephalitis - Irani, S; Sarosh R Irani (2010)
Voltage-gated potassium channel antibodies (VGKC-Abs) have been described in a spectrum of immunotherapy-responsive neurological diseases. These include neuromyotonia (NMT), a peripheral nervous system disease, limbic encephalitis (LE) a central nervous system disease, and Morvan's syndrome which affects both the peripheral and central nervous systems. Occasionally, these diseases can be associated with tumours. VGKC-Abs are defined by their ability to precipitate VGKCs from 2% digitonin-solubilised rabbit brain membranes labelled with 125I-α-dendrotoxin. α-dendrotoxin is known to bind Kv1.1, 1.2 and 1.6. We asked whether the clinical heterogeneity could be explained by the specificity of the patient antibodies for the different Kv1 channels. We received clinical data regarding 113 VGKC-antibody positive cases: 78 had LE/Epilepsy, 17 had NMT, 13 had MoS and five had other syndromes. In addition, we collected clinical data about 26 patients with a unique form of dystonic epilepsy in association with VGKC-Abs. Surprisingly, a series of biochemical and immunohistochemical experiments in both brain tissue and in Kv1-transfected cells showed that potassium channels were the target of only 3% of the 113 'VGKC'-Ab positive sera. We proposed that the 'VGKC'-antibodies were not directed against Kv1s but against other proteins in the 125I-α-dendrotoxin labelled rabbit brain complexes. Lgi1 (leucine-rich glioma inactivated 1), CASPR2 (contactin-associated protein 2) and contactin-2 were found within these complexes and, when individually expressed in a heterologous mammalian cell line, were found to be the direct target of the 'VGKC'-Abs. Lgi1-antibodies were found in 58% of the cases with LE/Epilepsy, 71% of the dystonic epilepsy patients and 15% of the MoS cases. By contrast, CASPR2 antibodies were found in 85% of the MoS, 61% of the NMT and 12% of the LE/Epilepsy cases. CASPR2 antibodies had a 99% negative predictive value for the presence of an underlying tumour. Contactin-2 antibodies were found uniquely in 2 of 113 cases. These findings describe novel antigenic targets which help to explain the clinical heterogeneity seen in 'VGKC-complex'-antibody associated diseases. In addition, they offer a method to predict the cases with underlying tumours. These findings have important implications for understanding the biology of these diseases.